Pancreatic resections for metastases: A twenty-year experience from a tertiary care center. Issue 5 (May 2020) - Di Franco, Gregorio; Gianardi, Desirée; Palmeri, Matteo; Furbetta, Niccolò; Guadagni, Simone; Bianchini, Matteo; Bonari, Federica; Sbrana, Andrea; Vasile, Enrico; Pollina, Luca Emanuele; Mosca, Franco; Di Candio, Giulio; et al.
Abstract: Background: Literature data about pancreatic resections for metastases are limited to small series, so that the role of surgery in this setting remains unclear. We herein report our experience from a tertiary care center, analyzing the outcomes of patients who underwent pancreatic resections for metastases and discussing the role of surgical resection in their management. Materials and methods: From January 1999 to January 2019, 26 patients underwent pancreatic resections for metastases from renal cell carcinoma (RCC-group) or other primitive tumors (non-RCC-group). Details regarding pre-, intra-, post-operative course, and follow-up, prospectively collected in a database of pancreatic resection, were retrospectively analyzed and compared. Results: RCC-group was composed of 21 patients, non-RCC-group of 5 patients. RCC-group presented a longer disease-free interval: 96.4 vs. 5.4 months (p < 0.001). In 9/21 patients (42.9%) of RCC-group the surgical resection of other organs or vascular structures was performed, while in non-RCC-group pancreatic resection alone was performed in all cases, p = 0.070. No local recurrence was reported in all cases. The systemic recurrence rate was 42.9% (9/21 patients) in RCC-group and 80% (4/5 patients) in non-RCC-group, p = 0.135. RCC-group presented a longer DFS and OS: 107.5 vs. 25.2 months (p = 0.002), and 109.1 vs. 36.2 months (p = 0.016), respectively. Conclusions: Radical pancreatic resection may confer a survival benefit for RCC metastases, while for other primitive tumors it should be applied more selectively. For RCC pancreatic metastases, an aggressive surgical approach, even in patient with locally advanced tumors, or associated extra-pancreatic localizations, or recurrent metastases should be taken in consideration.